Respuestas

2014-02-12T04:14:26+01:00
Primero sumas las dos x (2x+2x) = 4x

entonces queda
sen2x + sen4x = 0 

sen2x + 2sen2xcos2x = 0 

sen2x(1 + 2cos2x) = 0 

sen2x(1 + 2(2cos^2x - 1)) = 0 

sen2x(1 + 4cos^2x - 2) = 0 

sen2x(4cos^2x - 1) = 0 

sen2x = 0 ó 4cos^2x - 1 = 0 

sen2x = 0 ó 4cos^2x = 1 

sen2x = 0 ó cos^2x = 1/4 

sen2x = 0 ó cosx = + ó - 1/2 

2x = arcsen0; x = arccos - 1/2; x = arccos1/2 

x = 0; x = 30; 90; x = 60; x = 120; x = 180; x = 240 
mil gracias
tu sabes q el arccos es cos a la -1
si